Synergistic activity of repurposed peptide drug glatiramer acetate with tobramycin against cystic fibrosis Pseudomonas aeruginosa - Murphy,R; Coates,M; Thrane,S; Sabnis,A; Harrison,J; Schelenz,S; Edwards,A; Vorup-Jensen,T; Davies,J (Microbiology Spectrum, 2022)
Pseudomonas aeruginosa is the most common pathogen infecting the lungs of people with cystic fibrosis (CF), causing both acute and chronic infections. Intrinsic and acquired antibiotic resistance, coupled with the physical barriers resulting from desiccated CF sputum, allow P. aeruginosa to colonize and persist in spite of antibiotic treatment. As well as the specific difficulties in eradicating P. aeruginosa from CF lungs, P. aeruginosa is also subject to the wider, global issue of antimicrobial resistance. Glatiramer acetate (GA) is a peptide drug, used in the treatment of multiple sclerosis (MS), which has been shown to have moderate antipseudomonal activity. Other antimicrobial peptides (AMPs) have been shown to be antibiotic resistance breakers, potentiating the activities of antibiotics when given in combination, restoring and/or enhancing antibiotic efficacy. Growth, viability, MIC determinations, and synergy analysis showed that GA improved the efficacy of tobramycin (TOB) against reference strains of P. aeruginosa, reducing TOB MICs and synergizing with the aminoglycoside. This was also the case for clinical strains from people with CF. GA significantly reduced the MIC50 of TOB for viable cells from 1.69 mg/L (95% confidence interval [CI], 0.26 to 8.97) to 0.62 mg/L (95% CI, 0.15 to 3.94; P = 0.002) and the MIC90 for viable cells from 7.00 mg/L (95% CI, 1.18 to 26.50) to 2.20 mg/L (95% CI, 0.99 to 15.03; P = 0.001), compared to results with TOB only. Investigation of mechanisms of GA activity showed that GA resulted in significant disruption of outer membranes, depolarization of cytoplasmic membranes, and permeabilization of P. aeruginosa and was the only agent tested (including cationic AMPs) to significantly affect all three mechanisms.